KETERKAITAN ANTARA SUSU SEBAGAI PELENGKAP SARAPAN TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR - Stefani, Megah; Khoirunnisa, Fifi; Wulandari, Zulhijah (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2019)
The study aims to determine the association of milk as complimentary breakfast towards learning achievement of elementary school students, using a retrospective case-control research design. Subjects were determined purposively with the inclusion criteria having normal BMI and not lactose intolerance. The minimum number of subjects was based on calculations were 38 children. Subjects as many as 22 elementary school children were exposed to a complete breakfast habit with milk and 17 elementary school children became a control group for breakfast habits without milk. Completing the 2x24 hour food recall questionnaire and 7-day food record and subject interviews were conducted for 1 week. Learning achievement is measured using the final score of the semester 1 by K13 curriculum. There was a significant relationship in the exposed group and the control group on learning achievement especially Bahasa scores (p = 0,001) as many as 90,91% in the exposed group and 88,24%, in the control group, also, the tendency for a better IPA (Science) scores in the exposed group was 81,82% compared to the control group at 64,71%. Thus, the habit of breakfast supplemented with milk is closely related to the learning achievement of elementary school children.